The Influence of Digital Payment in Shaping The Consumption Behavior of Generation Z in Banjarmasin - Putri, Indira Ulfa Cahyani (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
This research aims to explore and describe the phenomenon of using digital payments and how this shapes consumption behavior among Generation Z in Banjarmasin City. Qualitative descriptive methods were used to describe this phenomenon, through interviews with 10 informants, each represented by 2 Generation Z in each sub-district in Banjarmasin City. The results of this research show that the use of digital payments not only has a practical impact in terms of ease of transactions, but also influences the mindset and consumption behavior of Generation Z by paying attention to factors such as security, comfort, time efficiency, as well as the ability to control impulse purchases, purchases irrationally, and wastefully. Overall, the use of digital payments is not only a means of transactions, but also forms a more modern and up-to-date consumption behavior pattern for Generation Z in Banjarmasin City.